Application of Pressure Type Curve Matching for Characterizing the Naturally Fractured Reservoir - Sri Feni Maulindani; Doddy Abdassah; Taufan Marhaendrajana; Suryo Prakoso; Muhammad Taufiq Fathaddin (Journal of Earth Energy Science, Engineering, and Technology, 2021)
Naturally fractured reservoirs have an important role in the production and reserves of hydrocarbons, where more than 40% of the oil and gas reservoir production comes from this reservoir type. There are two systems that affect the production mechanism in this reservoir, namely the matrix as a fluid source and fractures as a fluid transfer network to the wellbore. This study discusses the characterization of naturally fractured reservoirs using curve type matching. In this study, the Warren and Root model is applied to create a reservoir model that applies the fluid flow mechanism from the matrix to the fracture with pseudo steady state interporosity flow. Pressure transient analysis is commonly known and widely used by reservoir engineers as a tool to identify reservoir characteristics, where there are two important parameters that influence reservoir productivity, namely the ratio of the storativity coefficient (omega) and the interporosity flow coefficient (lamda). Based on the results of the analysis, it is found that the coefficients are strongly affected by the values of porosity fracture and permeability fracture also the productivity of the reservoir.